Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
This speculative narrative was composed as a teaching tool for Danish high school students (University of Southern Denmark, 2012) to help them reflect on how a community might respond to the presence of lifelike materials and ELT for the ISSP (Initiative for Science, Society and Policy). It was also published in the online design magazine Organs Everywhere (Armstrong, 2012f).